PENGARUH ASPEK-ASPEK KEPEMIMPINAN PARTISIPATIF KEPALA DESA TERHADAP PEMBANGUNAN PENDIDIKAN NONFORMAL - Husain, H. Walidun (JIV-Jurnal Ilmiah Visi, 2011)
The purpose of this research was to discover the influence of participative leadership aspects of village head either partially or simultaneously to the education development. The research was conducted in Gorontalo region in 2010 and the population BPD, LPM, village officials, elementary school and elementary school committee. The samples were selected by proportional random sampling technique and the main instrument employed rating scale tests in the form of close statements with alternative answers. To complete the discussion qualitatively, the research used interview technique for the Regent of Gorontalo district, the head of national education office, and other parties which considered important. After analyzing the data with path analysis, the research concluded, participative leadership aspects of village head either partially or simultaneously, give real contribution to education development.